(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article briefly examines the main aspects of the socio-political development strategy of the Republic of Uzbekistan. In particular, the effectiveness of the reforms carried out in this area and the constant improvement of the state’s material provision for the poor are discussed.